2021
DOI: 10.3389/fmed.2021.711027
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Severe COVID-19 Patients Admitted to an Intermediate Respiratory Care Unit

Abstract: Introduction: Many severe COVID-19 patients require respiratory support and monitoring. An intermediate respiratory care unit (IMCU) may be a valuable element for optimizing patient care and limited health-care resources management. We aim to assess the clinical outcomes of severe COVID-19 patients admitted to an IMCU.Methods: Observational, retrospective study including patients admitted to the IMCU due to COVID-19 pneumonia during the months of March and April 2020. Patients were stratified based on their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The univariate analysis revealed that surviving patients had a lower median age (68 (59-74) vs. 70.5 (67-76.5); p = 0.04), lower APACHE II score (19 (11-28) vs. 27.5 (22.5-30), p < 0.01), and higher median ROX H0-H8 score (6.49 (5.39-9.04) vs. 5.57 (4.86-6.97), p = 0.04) compared with the non-survivor group, as shown in Table 2 and Figure 2. There was not any difference in the median duration from hospitalization to ICU intubation (3 (2-7) vs. 4.5 (3)(4)(5)(6)(7)(8), p = 0.23) nor median IMCU length of stay (2.5 (1-4) vs. 2 (1-5), p = 0.84) between both groups, as shown in Table 2. The multivariate analysis showed the median ROX H0-H8 to be independently associated with ICU mortality as a protective factor, with an odds ratio (OR) (95% CI) = 0.77 (0.60-0.99), p < 0.05, and APACHE II (including age) as a risk factor OR (95% CI) = 1.09 (1.02-1.15), p < 0.05, as seen in Table 3.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The univariate analysis revealed that surviving patients had a lower median age (68 (59-74) vs. 70.5 (67-76.5); p = 0.04), lower APACHE II score (19 (11-28) vs. 27.5 (22.5-30), p < 0.01), and higher median ROX H0-H8 score (6.49 (5.39-9.04) vs. 5.57 (4.86-6.97), p = 0.04) compared with the non-survivor group, as shown in Table 2 and Figure 2. There was not any difference in the median duration from hospitalization to ICU intubation (3 (2-7) vs. 4.5 (3)(4)(5)(6)(7)(8), p = 0.23) nor median IMCU length of stay (2.5 (1-4) vs. 2 (1-5), p = 0.84) between both groups, as shown in Table 2. The multivariate analysis showed the median ROX H0-H8 to be independently associated with ICU mortality as a protective factor, with an odds ratio (OR) (95% CI) = 0.77 (0.60-0.99), p < 0.05, and APACHE II (including age) as a risk factor OR (95% CI) = 1.09 (1.02-1.15), p < 0.05, as seen in Table 3.…”
Section: Discussionmentioning
confidence: 86%
“…The development or upscaling of multidisciplinary intermediate care units (IMCU) has been proposed to relieve ICU units by taking charge of less severe patients and those who may be restricted from mechanical ventilation due to severe concomitant conditions [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve the best potential benefit of any NRT on HRF management, the patient should be allocated to a monitored setting, being cared for by personnel experienced in NRT. The IRCU is a suitable setting for this purpose where qualified respiratory staff can manage this situation with efficiency and less cost than the ICU [ 9 , 10 ]. Nevertheless, ensuring prompt endotracheal intubation is mandatory if the patient presents acute deterioration or no improvement after an NRT short trial.…”
Section: Discussionmentioning
confidence: 99%
“…There are scarce data regarding mortality in subjects with severe COVID-19, particularly in the RICU. Mortality varies widely among published series, ranging from 8 to 30% 11,14 .…”
Section: Mortality/therapeutic Limitmentioning
confidence: 99%
“…Recently, some studies reported positive results on non-invasive respiratory strategies (NIRS) in patients with COVID-19 in RICU [13][14][15] . During the pandemic, RICU increased exponentially with the aim of avoiding ICU congestion.…”
Section: Introductionmentioning
confidence: 99%